Effect of humidity on flow ability of specialty protein sources in nursery diets - Carney, E.E.; Groesbeck, C.N.; Goodband, Robert D.; Tokach, Michael D.; Nelssen, Jim L.; DeRouchey, Joel M.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
We conducted an experiment to determine the effects of humidity on angle of repose (flowabilty) of different specialty protein sources. Five specialty proteins sources were used: fish meal, powdered blood meal (AP301), granulated blood meal (AP301G), powdered spray-dried animal plasma (AP920), and granulated spray-dried animal plasma (Appetein). The specialty protein sources were added at 0, 2.5, 5, 7.5, and 10% to a 70:30 corn-soybean meal blend. The experiment was conducted in an environmentally controlled nursery to minimize temperature and humidity fluctuations. There were two relative humidity levels, 34 and 64%. All samples were placed in the barn 24 h before the experiment was conducted to allow acclimation to the conditions. Flow ability was then determined by measuring angle of repose. Angle of repose is the maximum angle in which a pile of ingredient retains its slope. A large angle of repose represents a steeper slope and poorer flow ability. There was a protein source × inclusion level × humidity interaction observed (P<0.01). Humidity increased angle of repose, decreasing flow ability. Angle of repose increased with increasing inclusions of powdered animal plasma and fish meal, resulting in poorer flow ability. Powdered blood cells did not affect angle of repose with increasing inclusion levels. Angle of repose decreased as granular animal plasma and blood cell inclusions increased, improving flow ability. In conclusion, specialty protein ingredients in powder form reduce flow ability, while granulated specialty protein sources improve flow ability.
Keywords: Swine; Feed manufacturing; Angle of repose; Humidity